Contribution of sport innovation the european economic growth - Silva Piñeiro, R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The European institutions have recognized the outstanding contribution to the sport sector is having on job creation, local economic development and intersectoral flows, becoming one of the pillars that allow help overcome the current difficulties due to the high resistance which has been shown in the environment of economic crisis we have been dragging. Sport can strengthen the socio-economic impact it has had, and even improve, through innovative services and products, which in any case must attend especially at the regional level, the key to success of any knowledge.